Economic Development, Public Policy &International Tourism: Empirical Evidence from Pakistan Economy - Furquan, Muhammad; Moin, Nighat; Ashraf, Muhammad Nabeel; Raees, Muhammad Bilal (The journal of contemporary issues in business and government, 2021)
Background:The tourism industry is considered to be a million-dollar industry with its ability to increase the cash flows and ability to sell things for higher prices than usual. Pakistan is a very lucrative country for travellers with an immense amount of diversity in culture as well as weather. There are a number of historic, adventurous, exotic, and peaceful spots in Pakistan to attract travellers and boost their tourism industry. Methods: This study aimed to examine the influence of international tourism receipts and expenditure on the gross domestic product of Pakistan& also recommend public policies. Time series data for twenty-four years was gathered in this study and regression analysis was applied to examine the hypothesized relationships. Results:Findings of this study have reflected the significant and positive impact of the hypothesized variables on the economy of Pakistan.